The effectiveness of artificial intelligence in contemporary digital graphic design (Al-Academy, 2023)
In our world, technological development has become inherent in all walks of life and is characterized by its speed in performance and uses. This development required the emergence of new technologies that represent a future revolution for a fourth industrial revolution in various fields, which contributed to finding many alternatives and innovative technical solutions that shortened time and space in terms of making Machines are smarter, more accurate, and faster in accomplishing the tasks intended for them, and we find the emergence of what is called artificial intelligence (artificial intelligence), which is the technology of the future, which is one of the most important outputs of the fourth industrial revolution, and artificial intelligence has become a comprehensive term for applications that perform complex tasks that required in the past human inputs such as Communicating with customers via the Internet and various digital applications, as it saved a lot of time, effort, and money thanks to its various capabilities, specifically in the field of graphic design. in graphic design The study aimed to identify the effectiveness of artificial intelligence in contemporary digital graphic design and to benefit from its applications through its employment in the field of graphic design. And the techniques used to design and develop artificial intelligence applications 4- The importance of artificial intelligence and its effectiveness in developing graphic design skills. Its effective capabilities enable and facilitate contemporary digital graphic design processes. The research also came out with conclusions, recommendations and proposals that came from it. Results: 1- Artificial intelligence for the graphic designer shortens the implementation of various designs and analyzes problems with accuracy and high speed, which allows achieving creativity and developing his skills. 2- Artificial intelligence can process a huge amount of data and information in a short period of time compared to time spent on traditional digital design. 3- Artificial intelligence enables the graphic designer to find solutions to unfamiliar problems that he faces when executing the design work. The researcher came out with conclusions, including: 1 - The revolution in the world of artificial intelligence in the future will make applications capable of carrying out various tasks of graphic design and most areas of our lives. 2- Artificial intelligence helps users create new patterns and different designs with less experience and knowledge in the field of design. The researcher also recommended directing graphic designers and students to work and make use of artificial intelligence techniques in the various stages of design to save time and effort and avoid making mistakes. The researcher also suggested studying the applications of artificial intelligence and their uses in the digital graphic achievement. The search was also included in the list of Arab and foreign sources